Políticas locais de desenvolvimento rural: uma análise do projeto campo forte e empreendedor no Município de Goioerê- Pr - Silva, Emerson Ferreira da (2023)
Rural agriculture has a relevant position in the production of most of the food consumed by people, in spite of suffering the effects of a conjuncture that is not favorable to it; therefore, it is important to value initiatives that meet the needs of this sector. In this background, this thesis aims to examine the potential and limitations of a local rural development policy at the municipal level, the Campo Forte e Empreendedor (CAFE) project, analyzing the feasibility of building paths that can contribute to overcoming the obstacles faced by peasant agriculture at the local level. The CAFE project was idealized by the Goioerê Commercial and Business Association, with the objective of promoting an action of the entity with the small rural producers of the municipality. The study was carried out using a qualitative methodology. The interviews and secondary data were analyzed, which made it possible to carry out a diagnosis of the CAFE project by means of the ex-ante analysis methodology, which allowed the identification of the project's strengths and weaknesses. For the ex-ante analysis, the tool used was the Problem Tree, which provided the construction of a GUT Matrix. It was found that the CAFE project has the potential to fulfill its proposed objectives. However, some inconsistencies in the project were also verified, such as the lack of financial predictability, which needs to be corrected in order for the project to be more assertive.